Catalyst-free Petasis-type reaction: Three-component decarboxylative coupling of boronic acids with proline and salicylaldehyde for the synthesis of alkylaminophenols. Issue 11 (14th March 2018) - Kaboudin, Babak; Zangooei, Ali; Kazemi, Foad; Yokomatsu, Tsutomu
Graphical abstract: Highlights: A simple and practical method for the synthesis of alkylaminophenols. Three-component reaction of proline with arylboronic acid and salicylaldehyde. Petasis-type reaction. Catalyst-free reaction, mild reaction conditions, and high selectivity. Abstract: A simple method is reported for the synthesis of alkylaminophenols in moderate to good yields via a three-component, catalyst-free decarboxylative coupling of proline with salicylaldehyde and boronic acids.